a survey on sentiment study in twitter data using Hadoop streaming API - Vyshnavi, R; Venkata Raju, K; Vamsi Krishna, G; Bhavya Shree, Y (International Journal of Engineering and Technology, 2017)
Twitter is an online individual with singular correspondence webpage that conveys created live of knowledge which is handled, by semi-formed and disheveled information. In this work, a system that accomplishes demand of tweets analysis in Twitter-API is talked relating to. to revamp its ability, it is planned to finish the work on the java-Hadoop system, a typically got coursed managing organize utilizing the Map cut back parallel composition purpose of the scan. At long last, wide examinations area unit about to be driven on evident educational gatherings, with a necessity to accomplish in every implies that really matters indefinite or lots of obvious truth than the planned systems in composing. The focus is providing the positive negative and neutral analysis by opinion Mining.Â Â